Upcoming progress of transcriptomics studies on plants: An overview - Tyagi, Parul; Singh, Deeksha; Mathur, Shivangi; Singh, Ayushi; Ranjan, Rajiv (Frontiers in Plant Science, 2022)
Transcriptome sequencing (RNA-Seq) is a high-throughput, sensitive, and high-resolution next-generation sequencing (NGS) approach used to study non-model plants and other organisms. In other words, it is an assembly of RNA transcripts from individual or whole samples of functional and developmental stages. RNA-Seq is a significant technique for identifying gene predictions and mining functional analysis that improves Gene Ontology understanding mechanisms of biological processes, molecular functions, and cellular components, but there is limited information available on this topic. Transcriptomics research on different types of plants can assist researchers to understand functional genes in better ways and regulatory processes to improve breeding selection and cultivation practices. In recent years, several advancements in RNA-Seq technology have been made for the characterization of the transcriptomes of distinct cell types in biological tissues in an efficient manner. RNA-Seq technologies are briefly introduced and examined in terms of their scientific applications. In a nutshell, it introduces all transcriptome sequencing and analysis techniques, as well as their applications in plant biology research. This study will focus on numerous existing and future-coming strategies for improving transcriptome sequencing for the mining of functional genes in most plants and breeding novel varieties that are based on the principles, development, and use of RNA-Seq technologies.